Investigation into the mechanism of action of the antimicrobial peptide epilancin 15X - Wu, Chunyu; Lower, B. Alexis; Moreira, Ryan; Dorantes, Darian; Le, Tung; Giurgiu, Constantin; Shi, Yanxiang; van der Donk, Wilfred A. (Frontiers in Microbiology, 2023)
Addressing the current antibiotic-resistance challenge would be aided by the identification of compounds with novel mechanisms of action. Epilancin 15X, a lantibiotic produced by Staphylococcus epidermidis 15X154, displays antimicrobial activity in the submicromolar range against a subset of pathogenic Gram-positive bacteria. S. epidermidis is a common member of the human skin or mucosal microbiota. We here investigated the mechanism of action of epilancin 15X. The compound is bactericidal against Staphylococcus carnosus as well as Bacillus subtilis and appears to kill these bacteria by membrane disruption. Structure-activity relationship studies using engineered analogs show that its conserved positively charged residues and dehydroamino acids are important for bioactivity, but the N-terminal lactyl group is tolerant of changes. Epilancin 15X treatment negatively affects fatty acid synthesis, RNA translation, and DNA replication and transcription without affecting cell wall biosynthesis. The compound appears localized to the surface of bacteria and is most potent in disrupting the membranes of liposomes composed of negatively charged lipids in a lipid II independent manner. Epilancin 15X does not elicit a LiaRS response in B. subtilis but did upregulate VraRS in S. carnosus. Treatment of S. carnosus or B. subtilis with epilancin 15X resulted in an aggregation phenotype in microscopy experiments. Collectively these studies provide new information on epilancin 15X activity.